Differences in serum cytokine levels distinguish between clinically non‐invasive lung adenocarcinoma and invasive lung adenocarcinoma: A cross‐sectional study - Bingjie Zeng; Xianzhao Wang; Yueyang Qin; Leiqun Cao; Congcong Zhang; Fanyu Meng; Changqiang Chen; Jiayi Wang; Lifang Ma (Health Science Reports, 2023)
Abstract Background Lung cancer incidence and mortality remain high and are now the leading cause of cancer‐related death. Lung adenocarcinoma (LUAD) is one of the main histological subtypes of lung cancer. Previous studies have shown the role of inflammation in the development of lung cancer, but the relationship between cytokines and LUAD is still unclear. To further differentiate and explore the association of cytokines with the risk of non‐invasive and invasive LUAD, we studied and assessed serum cytokine levels in patients with two types of LUAD. Methods A cohort study of 90 non‐invasive LUAD and 90 invasive LUAD was retrospectively included, and the clinical characteristics were recorded in detail. The differences in the levels of 12 serum cytokines (IFN‐α, IFN‐γ, IL‐10, IL‐12P70, IL‐17A, IL‐1β, IL‐2, IL‐4, IL‐5, IL‐6, IL‐8, and TNF‐α) between the two groups of patients with LUAD were analyzed and evaluated. And we evaluated the clinical value of cytokine differential diagnosis of invasive LUAD based on receiver operating characteristics (ROC) curves. Results The mean age of the patients was 56.6 years, and the proportions of males and females were 38.9% and 61.1%, respectively. IFN‐α, IL‐1β, IL‐2, IL‐6, TNF‐α, IL‐4, and IL‐8 were significantly increased in patients with invasive LUAD compared with the non‐invasive LUAD group. Further research found that smoking is an important factor, with changes in the four cytokines IL‐1β, IL‐6, IL‐8, and TNF‐α being significantly higher in the smoking group of patients with invasive LUAD. It can be seen from the area under the curve that IL‐1β and IL‐2 have a significant differential diagnosis. Conclusions We observed differences in preoperative serum cytokine levels between patients with invasive and non‐invasive LUAD, which may serve as potential serum biomarkers for clinical differential diagnosis and disease progression assessment.